2003
DOI: 10.4049/jimmunol.170.3.1231
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Escape of Subdominant CD8+ T Cells During Negative Selection Results in an Altered Antiviral T Cell Hierarchy

Abstract: Negative selection is designed to purge the immune system of high-avidity, self-reactive T cells and thereby protect the host from overt autoimmunity. In this in vivo viral infection model, we show that there is a previously unappreciated dichotomy involved in negative selection in which high-avidity CD8+ T cells specific for a dominant epitope are eliminated, whereas T cells specific for a subdominant epitope on the same protein preferentially escape deletion. Although this resulted in significant skewing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…2b, we show that the average antigenic distance between T cells and foreign peptides is decreased after negative selection. This finding agrees with the observation that negative selection increases the specificity that TCR have to foreign peptides [17][18][19]. …”
supporting
confidence: 92%
“…2b, we show that the average antigenic distance between T cells and foreign peptides is decreased after negative selection. This finding agrees with the observation that negative selection increases the specificity that TCR have to foreign peptides [17][18][19]. …”
supporting
confidence: 92%
“…Secondly, homology of the potential epitope with self-protein sequences might narrow the repertoire based on self-tolerance mechanisms either in the thymus or in the periphery. Thymic education has in fact been shown to influence the pattern of dominant and subdominant epitopes (62). We are currently investigating whether the nonimmunogenicity of roughly 50% of the high-affinity binders is due to homology with host proteins (which might have led to negative selection) by comparing the peptide sequences against the mouse proteome.…”
Section: Discussionmentioning
confidence: 99%
“…This will be particularly important in transgenic mouse models of cancer in which the mice are tolerant to the tumor Ag and the high-affinity T cells that can be generated to target the tumor in wild-type (nontolerant) mice will not be present (47,48). Makki et al (49) and Kedl et al (50) have shown that targeting an immunodominant tumor epitope can fail to result in a strong enough antitumor response that will result in the eradication of a tumor.…”
Section: Discussionmentioning
confidence: 99%